دور القطاع الخاص في تفعيل قيم العمل دراسة ميدانية بمؤسسة صناعية خاصة - زرفة, بولقواس (Sciences humaines; Vol. 24 (2012): SCIENCES HUMAINES)
ال ملخّـص: تهدف هذه الدراسة إلى تحليل نماذج لقيم العمل داخل مؤسسات القطاع الخاص،  التي أصبحت تنافس المؤسسات العمومية على أكثر من مستوى. وتوصلت الدراسة إلى مجموعة من النتائج أهمها: أن قيم الانضباط مشجعة ومدعمة لما يتوقع من هذا النوع من المؤسسات، كما أن قيم الصدق المقترحة جاءت كلها إيجابية، في حين قيم المسؤولية تخضع للعلاقات الإنسانية التي تربط العمال بصاحب المؤسسة.          كما كشفت الدراسة أن المسؤولية تجاه الانحرافات التي تحدث في ميدان العمل سلبية، لكن هذا لا يمنع من أن مؤسسات القطاع الخاص بإمكانها أن تلعب دور لا يستهان به في إحياء وتثمين قيم العمل لدى العامل الجزائري.   This study aims to analyze the models of work within the private sector institutions. The private institutions, which became the competitors of the public institutions on more than one level. The study revealed the following result: The values of discipline, are encouraging and supporting to what is expected from this type of institutions, and the values of honesty proposed, were all positive, while the values of responsibility relied on human relationships that the workers to the owner of the institution . The study also revealed that responsibility for deviations that occur in the field of work is negative, but this does not mean that the private sector cannot play a significant role in reviving and appreciating the work values of the Algerian worker.